2010
DOI: 10.1590/s1516-05722010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Produção de biomassa e óleo essencial de alecrim (Rosmarinus officinalis L.) em função da altura e intervalo entre cortes

Abstract: RESUMO:O alecrim é planta exótica e o interesse no seu cultivo tem crescido ao longo dos anos, pois pode ser utilizado tanto para fins medicinais como aromáticos; no entanto, o conhecimento fitotécnico sobre a espécie é bastante limitado. Dessa forma, o trabalho objetivou avaliar a influência da altura de corte e do intervalo destes sobre a produção de biomassa e no rendimento do óleo essencial de alecrim. O experimento foi realizado no Instituto Agronômico, em Campinas -SP, no período de janeiro de 2006 a jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
1
6
0
10
Order By: Relevance
“…Analyzing the effects of two plant age on the content of essential oil from the leaves of Melissa officinalis, Meira et al (2011) found that the essential oil content showed no significant difference between the periods evaluated, and the average oil content in the two cuts was 0.018%. Similarly, May et al (2010), while evaluating the production of essential oil of Rosmarinus officinalis at different plant ages, found that the yield of essential oil was not affected over time. The variation in oil content depending on the age of the plant appears to be a factor that varies with the species.…”
Section: Essential Oil Contentmentioning
confidence: 97%
See 1 more Smart Citation
“…Analyzing the effects of two plant age on the content of essential oil from the leaves of Melissa officinalis, Meira et al (2011) found that the essential oil content showed no significant difference between the periods evaluated, and the average oil content in the two cuts was 0.018%. Similarly, May et al (2010), while evaluating the production of essential oil of Rosmarinus officinalis at different plant ages, found that the yield of essential oil was not affected over time. The variation in oil content depending on the age of the plant appears to be a factor that varies with the species.…”
Section: Essential Oil Contentmentioning
confidence: 97%
“…Santos et al (2012) studied the plant age (3, 6, 9 and 12 months) on the chemical composition of the essential oil of A. zerumbet and verified variations in chemical composition of this oil between six and nine months. However, May et al (2010) evaluated the quality of the essential oil of R. officinalis, and concluded that the concentrations of active ingredients of essential oil of this species were not affected by the plant age.…”
Section: Quality Of the Essential Oilmentioning
confidence: 99%
“…O alecrim (Rosmarinus officinalis L.), pertencente à família Lamiaceae (Labiatae), tem sua origem no Sul da Europa e Norte da África (MARTINS et al, 1998). De acordo com relatos encontrados na literatura, esta planta pode apresentar propriedades estomacais, estimulantes, antiespasmódica, emenagogas e cicatrizantes (MAY et al, 2010). May et al (2010) define esta planta como um subarbusto muito ramificado, sempre verde, com hastes lenhosas, folhas pequenas, sésseis, finas, opostas e lanceoladas, de sabor picante.…”
Section: Alecrim (Rosmarinus Officinalis)unclassified
“…O alecrim (Rosmarinus officinalis L.) é planta pertencente à família Lamiaceae A composição dos óleos essenciais das plantas é determinada pela espécie: variedade, período de colheita e tipo de processamento (Guillénet al, 1996 (MAY, et al, 2010).…”
Section: Introductionunclassified